A meta-synthesis of policy recommendations regarding human mobility in the context of climate change - Schwerdtle, Patricia; Stockemer, Julia; Bowen, Kathryn J.; Sauerborn, Rainer; McMichael, Celia; Danquah, Ina (International journal of environmental research and public health, 2020)
Changing mobility patterns combined with changes in the climate present challenges and opportunities for global health, requiring effective, relevant, and humane policy responses. This study used data from a systematic literature review that examined the intersection between climate change, migration, and health. The study aimed to synthesize policy recommendations in the peer-reviewed literature, regarding this type of environmental migration with respect to health, to strengthen the evidence-base. Systematic searches were conducted in four academic databases (PubMed, Ovid Medline, Global Health and Scopus) and Google Scholar for empirical studies published between 1990–2020 that used any study design to investigate migration and health in the context of climate change. Studies underwent a two-stage protocol-based screening process and eligible studies were appraised for quality using a standardized mixed-methods tool. From the initial 2425 hits, 68 articles were appraised for quality and included in the synthesis. Among the policy recommendations, six themes were discernible: (1) avoid the universal promotion of migration as an adaptive response to climate risk; (2) preserve cultural and social ties of mobile populations; (3) enable the participation of migrants in decision-making in sites of relocation and resettlement; (4) strengthen health systems and reduce barriers for migrant access to health care; (5) support and promote optimization of social determinants of migrant health; (6) integrate health into loss and damage assessments related to climate change, and consider immobile and trapped populations. The results call for transformative policies that support the health and wellbeing of people engaging in or affected by mobility responses, including those whose migration decisions and experiences are influenced by climate change, and to establish and develop inclusive migrant healthcare.